An evaluation of PROMIS health domains in adults with haemophilia: A cross‐sectional study. Issue 3 (18th April 2021) - Barry, Vaughn; Buckner, Tyler W.; Lynch, Mary Ellen; Figueroa, Janet; Mattis, Shanna; Stout, Mary E.; Kempton, Christine L.
Abstract: Introduction: The Patient‐Reported Outcomes Measurement Information System (PROMIS) provides measures of health status that assess physical, mental and social well‐being from the patient perspective. PROMIS measures are used in clinical practice and research across various patient populations but are not yet validated among patients with haemophilia. Aim: Evaluate the sensitivity of PROMIS to indicators of haemophilia clinical severity and compare PROMIS measures to those from other PRO instruments. Methods: Male adults with haemophilia (n = 115) completed the PROMIS‐29 short form which includes 4 questions for each of 7 domains: depression, anxiety, ability to participate in social roles and activities, physical function, pain interference, fatigue and sleep disturbance. Participant responses for each domain were scored on a T‐score metric with a mean of 50 and a standard deviation of 10 based on the original PROMIS reference sample of US adults. Participants also completed other generic and haemophilia‐specific health‐related quality of life questionnaires. Results: Participants who experienced higher pain and depression levels reported significantly worse health in every PROMIS domain compared with their peers. Those who had recently needed to use crutches, visit an emergency department or were currently unemployed or disabled also reported poor PROMIS scores on most domains. Construct validity was supported by correlations between PROMIS domain scores and domain scores reported using the EQ‐5D‐5L and Haem‐A‐QoL. Conclusion: The PROMIS instrument provides a potentially valuable tool to evaluate the impact of haemophilia and suggests usefulness in research and clinical practice.